A just energy transition : getting decarbonisation right in a time of crisis - Atkins, Ed (Lecturer on environment) (Bristol University Press, 2023)
To reduce emissions and address climate change, we need to invest in renewables and rapidly decarbonise our energy networks. However, decarbonisation is often seen as a technical project, detached from questions of politics and social justice. What if this is leading to unfair transitions, in which some people bear the costs of change whilst others benefit? In this timely and expansive book, Ed Atkins asks are we getting decarbonisation right? And how could it be made better for people and communities? In doing so, this book proposes a different type of energy transition. One that prioritises and takes opportunities to do better - to provide better jobs, community ownership and improve people's homes and lives.